Gastric GIST: A Rare Cause of Upper GI Bleeding (Journal of Shaheed Suhrawardy Medical College, 2022)
Gastrointestinal stromal tumours are the most common mesenchymal tumours of the gastrointestinal tract. This case report highlights the necessity of early surgical intervention in such cases to avoid mortality due to bleeding and to raise the awareness of rare causes of upper gastrointestinal bleed and their management. A 19 year old male presented in the surgery department of Shaheed Suhrawardy medical College Hospital with complaints of recurrent episodes of melena with anorexia and weight loss for 6 months. Apart from anaemia no significant findings were noted on physical examination. Investigations including upper GI endoscopy was not conclusive. So he underwent laparotomy which revealed an exophytic growth along the lesser curvature. Lower partial gastrectomy was done and histopathological and immunohistochemistry report showed evidence of benign low risk GIST. As the tumor was benign with no malignant potential imatinib therapy was not advocated.J Shaheed Suhrawardy Med Coll 2020; 12(2): 119-122